ENGLISH PHRASEOLOGICAL UNITS AS EFFECTIVE MEANS OF ENHANCING VOCABULARY: ENGLISH PHRASEOLOGICAL UNITS AS EFFECTIVE MEANS OF ENHANCING VOCABULARY - Ismaylova, Aziza (Журнал иностранных языков и лингвистики, 2025)
The English language is abundant in phraseological units (PUs), which encompass idioms, collocations, and fixed expressions. These units are vital for natural and fluent language use, thereby playing a critical role in effective communication [12; 9]. Despite their significance, language learners frequently struggle with PUs due to their idiomatic nature and context-specific usage [4; 12]. Hence, there is an increasing interest in leveraging PUs as effective means to enhance vocabulary acquisition. This article examines the importance of PUs in vocabulary development, their cognitive and communicative benefits, and practical strategies for implementing them in language education.